Modeling in Biomedical Informatics – An Exploratory Analysis (Part 1) - Hasman, A.; Haux, R. (Methods of Information in Medicine, 2006)
Objectives: Modeling is a significant part of research, education and practice in biomedical and health informatics. Our objective was to explore, which types of models of processes are used in current biomedical/ health informatics research, as reflected in publications of scientific journals in this field. Also the implications for medical informatics curricula were investigated.Methods: Retrospective, prolective observational study on recent publications of the two official journals of the International Medical Informatics Association (IMIA), the International Journal of Medical Informatics (IJMI) and Methods of Information in Medicine (MIM).Results: 384 publications have been analyzed, 190 of IJMI and 194 of MIM. In regular papers (69 in IJMI, 62 in MIM), analyzed here in part 1, all of these model types could be found. In many publications we observed a mixture of models, being used to solve the ‘core’ research questions and also to systematically evaluate the research done. Knowledge of (and models for) software engineering and project management are also often needed. IJMI seems to have a closer focus on research concerning health information systems and electronic patient records, with a strong emphasis on evaluation. MIM seems to have a broader range of research approaches, including also statistical modeling and computational intensive approaches. The aim to provide solutions for problems related to data, information and knowledge processing and to study the general principles of processing data, information and knowledge in medicine and health care in order to contribute to improve the quality of health care, and of research and education in medicine and the health sciences was given in all publications.Conclusions: Modeling continues to be a major task in research, education and practice in biomedical and health informatics. Knowledge and skills concerning a broad range of model types is needed.
Keywords: Modeling; biomedical informatics; medical informatics; health informatics